Stroke metric changes pre- vs. postroutine anesthesiologist involvement for endovascular treatment of acute ischemic stroke - Rall, Natalie; Orr, Walter N.; Nazir, Niaman; Giron, Grace; Plaza, Erin (Frontiers in Anesthesiology, 2024)
Background Timing of endovascular treatment (EVT) for acute ischemic stroke (AIS) is important for achieving improved patient outcomes. Studies have evaluated how the type of anesthesia administered may impact the timing of EVT for AIS and patient outcomes, but there is limited data regarding how the presence of an anesthesia team can influence these metrics. Against this background, this study aims to compare time metrics and patient outcomes pre- vs. postroutine involvement of a dedicated anesthesia team dealing with EVT cases. Methods All patients at our institution who were between 18 and 100 years of age and evaluated for stroke and determined to be candidates for EVT during the period between November 2018 and November 2020 were considered for this study. Time metrics associated with EVT, which are commonly tracked by stroke centers, were compared pre- vs. postroutine involvement of a dedicated anesthesia team dealing with EVT cases. Secondary outcomes were a modified Rankin scale at time of discharge, an NIH Stroke Scale score at time of presentation and discharge, and incidence of intraprocedural hypotension. Results A total of 255 patients were included. A comparison of pre- (n = 119) vs. postneuroanesthesia team involvement (n = 136) in EVT for AIS revealed a statistically significant decrease in median time from puncture to TICI score >2b in the in-house group from 49.00 min preinvolvement to 23.00 min postinvolvement (P = 0.02) and puncture to TICI >2b (39.5 vs. 34 min, P = 0.01) for all patient categories when controlling for anesthesia type. The rate of incidence of intraprocedural hypotension (mean arterial pressure < 65 mmHg) also decreased significantly from 79% to 44% (P = 0.04), although it was not significant when controlling for anesthesia type (P = 0.05). Conclusions Routine involvement of a dedicated anesthesia team for EVT in patients with AIS could potentially improve stroke metrics and patient outcomes, although more studies are necessary to validate this model of care.